1996
DOI: 10.2500/105065896781794932
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Some Preservative Agents on Rat and Guinea Pig Tracheal and Human Nasal Ciliary Beat Frequency

Abstract: Many preservatives commonly included in nasal drops and sprays are known to impair mucociliary clearance. We studied the effects of four frequently used preservatives on ciliary beat frequency (CBF) in respiratory tissue. Sodium metabisulfite and chlorbutol did not change the CBF at concentrations up to 50 mg/L in rat tracheal mucosa. Chlorocresol 25 mg/L and 50 mg/mL reversibly decreased CBF (by 33% and 68%, respectively) in 60 minutes. Benzalkonium chloride impaired CBF irreversibly already at a relatively l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…To our knowledge there is one investigation assessing the ciliotoxicity of pure BAC on human nasal ciliated cells. 16 In agreement with the results of this investigation, a pronounced ciliotoxicity of BAC was observed in this human ex vivo model. After application of 0.025% BAC solution, almost complete ciliary arrest was observed within 60 minutes.…”
Section: Ciliary Activity Of Human Nasal Respiratory Epitheliasupporting
confidence: 91%
See 2 more Smart Citations
“…To our knowledge there is one investigation assessing the ciliotoxicity of pure BAC on human nasal ciliated cells. 16 In agreement with the results of this investigation, a pronounced ciliotoxicity of BAC was observed in this human ex vivo model. After application of 0.025% BAC solution, almost complete ciliary arrest was observed within 60 minutes.…”
Section: Ciliary Activity Of Human Nasal Respiratory Epitheliasupporting
confidence: 91%
“…In several in vitro investigations using tracheal explants of chicken embryos, guinea pigs, and rats, BAC, in concentrations ranging between 0.01 and 0.02%, revealed in part pronounced ciliotoxic effects. [13][14][15][16] Also, in human tissue specimens such as adenoids or isolated nasal epithelia, BAC proved ciliotoxic in concentrations common in commercially available nasal preparations. 16,17 In some animal experiments, alterations of the mucociliary transport system after BAC application have been found.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…BKC showed in different animal models such as chicken embryo tracheas, rat and guinea pig tracheal tissue the inhibitory effect on CBF. This effect is dose and time dependent with ciliostasis and ciliotoxicity as the ultimate response [ 210 , 211 ]. In vivo histological examinations in rats showed that BKC can also provoke nasal lesions.…”
Section: Toxicological Challenges Of Intranasal Applicationmentioning
confidence: 99%
“…Adverse effects reported in in vitro studies were (1) a reduction in the ciliary beat frequency of chicken embryonal tracheas and human adenoids [5][6][7][8] as well as in the human nasal mucosa [9]; (2) a time-and concentration-dependent destruction of the human respiratory mucosa in tissue culture and inhibition of human neutrophil actin polymerization, degranulation, and oxidative bursts [10], and a decrease in the velocity of transport of graphite particles and an irreversible prevention of the mucociliary transport of the frog palate [11,12]. The reason for these adverse effects may be explained by the differences in the design of these studies and the subjects used (rodents or humans).…”
Section: Discussionmentioning
confidence: 99%